نظام انصاف کے بارے میں اسلامی نقطہ نظر - Shahid, Umer; Hassani, Prof. Dr. Nawaz (Al-Irfan, 2022)
Islam is the religion of nature. Whether nature is related to man or the universe, the image of beauty and balance and proportion and moderation is very clear and prominent in it. Justice is a prominent attribute among the attributes of God, which is manifested in all the manifestations of life and creation. The various creatures and phenomena of this universe exist and are maintained due to nature of justice. Since man is the highest of creations, he has the greatest need to understand and accept justice. The aspect of justice is prominent in the invitation of the Prophets. In this world of colors and smells, which have been given to man with the powers and powers of discernment and will, justice requires that the ranks of this universe be wrapped up and a day be established where the judgment of human actions will be judged with justice. The concept of justice in Islamic Sharia consists of two components. One is that balance and proportion should be established in various rights and privileges among mankind. Others are that everyone should be given their rights and their rights should be ensured. Without this concept of justice, an individual or a society or a state faces fatal and serious consequences. Justice is very important in human life. Justice is the lifeblood of society. If justice goes out of life, then human life becomes hell. Everyone should be given their designated place and respect in the home, relatives and society. Parents, close relatives, neighbors, teachers, weak people of the society and the poor, the young, the rights of all are defined in Sharia and social traditions. Social justice is about giving everyone their rights.